Academic Trajectories of College Students with and without ADHD: Predictors of Four-Year Outcomes. Issue 6 (2nd November 2021) - DuPaul, George J.; Gormley, Matthew J.; Anastopoulos, Arthur D.; Weyandt, Lisa L.; Labban, Jeffrey; Sass, Aliza Jaffe; Busch, Chelsea Z.; Franklin, Melanie K.; Postler, Kaicee B.
ABSTRACT: Objective : Completing a college degree is associated with success in employment, financial earnings, and life satisfaction. Mental health difficulties, including attention-deficit/hyperactivity disorder (ADHD), can compromise degree completion. Method : We examined 4-year academic performance trajectories of 201 college students with ADHD (97 receiving medication [ADHD-Med], 104 not receiving medication [ADHD-NoMed]) relative to 205 non-ADHD Comparison students. Demographic (e.g., sex, race/ethnicity), psychological (e.g., self-reported depression and anxiety symptoms), and service-related (e.g., receipt of academic support) variables were included as predictors of intercept (i.e., Year 1 performance) and slope (yearly change) of semester GPA, progress toward graduation, and self-reported study skill strategies. Results : College students with ADHD obtained significantly lower GPAs (Hedge's g = −0.46 and −0.63) and reported less frequent use of study skills strategies (Hedge's g range from −1.00 to −2.28) than Comparison students. Significantly more Comparison students (59.1%) persisted through eight semesters relative to ADHD-NoMed students (49%). Multiple variables predicted outcomes with parent education, fewer depressive symptoms, better executive functioning, and receipt of high school Section 504 accommodations and college academic support services among the strongest predictors. Conclusions : Findings suggest support services for students with ADHD should begin prior to college matriculation and focus on improving executive functioning skills and depressive symptoms to increase chances of academic success.